SUPERVISI PENGAJARAN OLEH KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU PADA SMA TARBIYAH LABUHAN HAJI ACEH SELATAN - Nurul Fitri, Khairuddin, Niswanto. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: The implementation of supervision in education field is one factor to improve the pedagogical competence of teachers. The purpose of this study was to find out the supervision program, the implementation of teaching supervision, and the follow-up of teaching supervision by the principal in improving pedagogical competence of teachers in Tarbiyah Senior High School of Labuhan Haji of Aceh Selatan. The method used in this study was descriptive method with qualitative approach. The techniques of data collection were observation, interview, and documentation study. The subjects of this study were principals and teachers. The results of this study showed that: (1) The program of supervision in improving the pedagogical competence of teachers has been arranged and documented, but was not complete and only an outline. The program arranged included the annual and semestral work program. The principal kept implementing supervision activity, carrying out guidance, counseling, and directing teachers to improve their pedagogical competence. (2) The implementation of supervision carried out led to the effort of improving pedagogical competence of teachers. The activities carried out included class counseling, class observation, documentation, interview, questionnaire, and written report. (3) The follow-up of teaching supervision was by seeking for solution for the obstacles found in the implementation of supervision, such as the difficulty in time management to class visiting. Every finding that led to the restraint of teachers’ effort in improving pedagogical competence was always been followed up and responded by the principal. In following up the result of supervision, the principal has been gone through educative and persuasive approach, such as guiding teachers that had difficulties with discussion, case conference, between supervisor and the teachers about the obstacles faced in improving their teaching ability.Keywords: Teaching Supervision, Principal, and Pedagogy of Teacher Abstrak: Pelaksanaan supervisi di lingkungan pendidikan merupakan salah satu faktor yang ikut meningkatkan kompetensi pedagogik guru. Tujuan penelitian ini untuk mengetahui program supervisi, pelaksanaan  supervisi, dan tindak lanjut supervisi pengajaran oleh kepala sekolah untuk meningkatkan kompetensi pedagogik guru pada SMA Tarbiyah Labuhan Haji Aceh Selatan. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Teknik  pengumpulan data: observasi, wawancara dan studi dokumentasi. Subjek penelitian ini  adalah:  kepala   sekolah  dan   guru.   Hasil  penelitian   menunjukkan   bahwa: 1)  Program supervisi dalam meningkatkan kompetensi pedagoik guru telah disusun dan  terdokumentasi, namun program tersebut tidak lengkap dan hanya secara garis besarnya saja. Program yang disusun meliputi program kerja tahunan dan semesteran. Kepala sekolah tetap melaksanakan kegiatan supervisi, mengadakan pembinaan, membimbing,  dan  mengarahkan  guru   untuk peningkatan kemampuan pedagogiknya. 2) Pelaksanaan supervisi yang dilaksanakan dan telah mengarah pada upaya peningkatan kompetensi pedagogik guru. Kegiatan yang dilaksanakan meliputi bimbingan kelas, observasi kelas, dokumentasi, wawancara, angket, dan laporan tertulis. 3) Tindak lanjut supervisi pengajaran adalah dengan menindaklanjuti kendala yang ditemui dalam pelaksanaan supervisi yaitu susahnya pengaturan waktu untuk kunjugan kelas. Setiap adanya temuan yang mengarah pada terkendalanya upaya guru dalam meningkatkan kompetensi pedagogik, senantiasa ditindaklanjuti dan direspon dengan baik oleh kepala sekolah. Dalam menindaklanjuti hasil supervisi, kepala sekolah sudah melakukan pendekatan edukatif dan persuasif seperti pembinaan terhadap guru yang mengalami kesulitan melalui diskusi, konferensi kasus, tanya jawab antara supervisor dengan guru tentang kendala-kendala yang dihadapi dalam meningkatkan kemampuan mengajarnya.Kata Kunci: Supervisi Pengajaran, Kepala Sekolah dan Pedagogik Guru